HUBUNGAN STATUS GIZI DENGAN KEJADIAN PNEUMONIA PADA ANAK DI KABUPATEN LOMBOK UTARA PROVINSI NUSA TENGGARA BARAT (NTB) - Renaldo Tegar Prasetyo; Ananta Fittonia Benvenuto; Suci Nirmala; Sahrun (Nusantara Hasana Journal, 2023)
Pneumonia is a disease that attacks the lung tissue and is characterized by coughing and difficulty breathing which causes a wide spectrum of disease from mild to severe and deadly infections, depending on the causative pathogen. Nutritional status is a factor that is indirectly related to the incidence of pneumonia in children. Nutritional status has an important role in the child's immune system, malnutrition will be associated with a condition of decreased immune system so that various diseases can arise easily. The purpose of this study was to determine the relationship between nutritional status and the incidence of pneumonia in children in North Lombok District, NTB Province. The method used in this research is observational quantitative analytic research with a cross sectional study design. The sampling technique used consecutive sampling. The research was conducted at the District Hospital and all Community Health Centers in North Lombok Regency in April 2023. The research sample was 75 respondents. The data obtained were analyzed by Chi Square test. The significance value limit is (p≤ 0.05). The study showed that from 75 respondents, 57 people (76.0%) had positive pneumonia with malnutrition. The results of the bivariate analysis showed that the p - value < 0.05 (p - value = 0.03). There is a significant relationship between nutritional status and the incidence of pneumonia in children in North Lombok, West Nusa Tenggara.